Single nanoparticle detection in ionic liquids - Tanner, E; Batchelor-McAuley, C; Compton, R (American Chemical Society, 2016)
Nanoimpacts are novelly observed in a room temperature ionic liquid with the oxidation of silver nanoparticles in 1-butyl-3-methylimidazolium tetrafluoroborate. The addition of chloride facilitates the oxidation of the silver nanoparticles to silver chloride, which is observed as spikes in the current that correspond to single nanoparticles occurring via nanoimpacts, whereby random diffusion (Brownian motion) brings particles to within electron tunnelling distance of an electrode. © 2016 American Chemical Society.